Monolayer Nanosheets with an Extremely High Drug Loading toward Controlled Delivery and Cancer Theranostics - Peng, Liuqi (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.